2018
DOI: 10.1111/infa.12243
|View full text |Cite
|
Sign up to set email alerts
|

Increases in Arousal are More Long‐Lasting than Decreases in Arousal: On Homeostatic Failures During Emotion Regulation in Infancy

Abstract: In emotion regulation, negative or undesired emotions are downregulated, but there are also opponent processes to emotion regulation—in which undesired emotions are exacerbated dynamically over time by processes that have an amplifying or upregulating impact. Evidence for such processes has been shown in adults, but little previous work has examined whether infants show similar patterns. To examine this, we measured physiological arousal in 57 typical 12 month olds while presenting a 20‐min mixed viewing batte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 73 publications
1
8
0
Order By: Relevance
“…Previous research has shown that, when infants are sitting on their parents' lap watching an experimental test battery, with the parents asked to restrain the infant if they try to get down, then only high arousal states are more persistent than expected (Wass et al, 2018). Our findings are consistent with this, but suggest that, in naturalistic home settings, both low-and high arousal states are more persistent than expected.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Previous research has shown that, when infants are sitting on their parents' lap watching an experimental test battery, with the parents asked to restrain the infant if they try to get down, then only high arousal states are more persistent than expected (Wass et al, 2018). Our findings are consistent with this, but suggest that, in naturalistic home settings, both low-and high arousal states are more persistent than expected.…”
Section: Discussionsupporting
confidence: 86%
“…This series of events -being abruptly told 'no', a tug of war, the toy breaking, being stared at by strangers -are all triggered by the child's behaviour, as a function of their arousal state (Cole et al, 2017). But they are also independent, exogenous causes of further increases arousal -a positive feedback look (Potegal et al, 2009;Wass et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research has questioned whether allostastic mechanisms actually influence real-world arousal patterns at all during early development. One study examined day-long recordings of arousal fluctuations in infants 138 (see also 139 (see Figure 4)). Based on allostasis, they predicted that, if fluctuations above and below the mean are corrected for via self-regulation, then high or low arousal states should be more short-lived than intermediate arousal states.…”
Section: Temporal Regularitiesmentioning
confidence: 99%
“…In previous research we took a different method: rather than taking an event-locked approach, we instead analysed spontaneous fluctuations in arousal during the presentation of ageappropriate (and not deliberately anxiogenic) static and dynamic viewing materials (Wass, Clackson, & Leong, 2018). Arousal was measured via a composite of peripheral measures of physiological arousal including electrocardiography (inter-beat interval), heart rate variability, electro-dermal activity and movement.…”
Section: Introductionmentioning
confidence: 99%